2009
DOI: 10.1186/1471-2180-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining chemical genomics screens in yeast to reveal spectrum of effects of chemical inhibition of sphingolipid biosynthesis

Abstract: BackgroundSingle genome-wide screens for the effect of altered gene dosage on drug sensitivity in the model organism Saccharomyces cerevisiae provide only a partial picture of the mechanism of action of a drug.ResultsUsing the example of the tumor cell invasion inhibitor dihydromotuporamine C, we show that a more complete picture of drug action can be obtained by combining different chemical genomics approaches – analysis of the sensitivity of ρ0 cells lacking mitochondrial DNA, drug-induced haploinsufficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…Upregulation of multidrug resistance genes is a common response of yeast to xenobiotics. The resistance of yeast to ϳ25% of all compounds tested (19,22) is dependent on the upregulation of these genes. Although several multidrug resistance transporters are upregulated after diclofenac exposure, a single ABC transporter, Pdr5p, is crucial in diclofenac resistance (Fig.…”
Section: Vol 77 2011mentioning
confidence: 98%
“…Upregulation of multidrug resistance genes is a common response of yeast to xenobiotics. The resistance of yeast to ϳ25% of all compounds tested (19,22) is dependent on the upregulation of these genes. Although several multidrug resistance transporters are upregulated after diclofenac exposure, a single ABC transporter, Pdr5p, is crucial in diclofenac resistance (Fig.…”
Section: Vol 77 2011mentioning
confidence: 98%
“…29, 30 Recent studies have also found the production of EVs aid in the development of biofilms by some strains. 31, 32 Despite the widespread production and activity of EVs, much still remains to be learned about the mechanisms controlling their biogenesis. 25, 28, 30 …”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling can be used in order to simulate the perturbation of ceramide and S1P levels, generating in silico disease models in yeast. The predictions of these models can be validated easily in yeast and then translated to complex mammalian systems [188]. …”
Section: Future Perspective: Exploiting Yeast To Elucidate Sphingolipmentioning
confidence: 99%
“…The effects of this perturbation can be analyzed in the context of the available yeast metabolome, transcriptome, proteome and interactome data [189193]. Lipidomic analyses may identify specific (and unexpected) metabolites that are important in maintaining homeostasis and that may be altered in disease conditions [188]. Recent advances with mass spectrometric tools in the field of lipidomics have made it possible to identify and quantify many species of sphingolipids.…”
Section: Future Perspective: Exploiting Yeast To Elucidate Sphingolipmentioning
confidence: 99%